Electric Vehicle Purchase Intentions Among Millennials in Jabodetabek: An Analysis of the Theory of Planned Behavior and Motivation with Gender as a Moderator - Via Afrianti; Ma’mun Sarma; Indra Refipal Sembiring (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Global warming can be caused by various sectors, one of which is the transportation sector. The use of gasoline is one of the main contributors to energy consumption. Conventional cars typically use gasoline as fuel to support the mobility of their users. The use of this fuel can have negative impacts on the environment, such as greenhouse gas emissions and air pollution. Therefore, electric vehicles could be a potential solution to reduce these impacts. However, it cannot be denied that there are several barriers to the adoption of electric vehicles. Through the Theory of Planned Behavior (TPB) analysis, this study explores the influence of attitudes toward behavior, subjective norms, and perceived behavioral control on the intention to purchase electric vehicles among millennials. Additionally, it examines the motivations of millennials in their purchase intentions and the moderating role of gender in the intention to buy electric vehicles. The study sample consists of millennials living in the Jabodetabek area with an interest in electric vehicles. A quantitative method with a Structural Equation Modeling (SEM)-PLS approach is used to analyze the relationships among the variables studied. The results show that TPB and motivation influence the intention to purchase electric vehicles among millennials in Jabodetabek. Meanwhile, gender moderation only influences the relationship between perceived behavioral control and the intention to buy electric vehicles among millennials in Jabodetabek.